IMPLEMENTASI GRAF MENGGUNAKAN QGIS UNTUK EFISIENSI PROMOSI DENGAN METODE SHORTEST PATH BERBASIS DESKTOP - Prabowo Wiguna, Dede (Journal of Computer Science and Technology (JCS-TECH), 2025)
Graph theory serves as the foundation for creating representations of a network's connectivity. With graph theory, routing algorithms such as the shortest path method can be developed, which can help optimize finding the best route. Thus, solving problems related to the most optimal distance, time, and cost can be easily and effectively addressed. This research uses the shortest path method with the help of QGIS Desktop. The goal is to find the best route in terms of distance (shortest) and time (fastest) so that the pemasaran division can easily determine the promotional targets at schools that are prioritized for visits. The results of this study indicate that the primary promotion targets to be visited are SMA Raksana and Yayasan Pendidikan Harapan 1 Medan, which are approximately 3.1-3.2 km away. If compared to the schools that are not a priority to visit (not potential), namely SMA/SMK Advent, because its distance is ± 6.9 km, making it the farthest from other schools that are the focus of this research.